2019
DOI: 10.5761/atcs.oa.19-00128
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind Randomized Controlled Trial to Determine the Preventive Effect of Hangekobokuto on Aspiration Pneumonia in Patients Undergoing Cardiovascular Surgery

Abstract: Purpose: This study aimed to assess whether hangekobokuto (HKT) can prevent aspiration pneumonia in patients undergoing cardiovascular surgery.Methods: We performed a single-center, double-blinded, randomized, placebo-controlled study of HKT in patients undergoing cardiovascular surgery. JPS HKT extract granule (JPS-16) was used as HKT. The primary endpoint was defined as the prevention of postoperative aspiration pneumonia. The secondary endpoints included complete recovery from swallowing and coughing disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Recently, another double-blinded randomized control study demonstrated the effect of hangekobokuto in reducing aspiration pneumonia [33]. In this study conducted with patients undergoing cardiovascular surgery, the proportion of subjects with postoperative aspiration pneumonia was significantly lower in the hangekobokuto group than in the placebo group (P = 0.017).…”
Section: Figure 11mentioning
confidence: 74%
“…Recently, another double-blinded randomized control study demonstrated the effect of hangekobokuto in reducing aspiration pneumonia [33]. In this study conducted with patients undergoing cardiovascular surgery, the proportion of subjects with postoperative aspiration pneumonia was significantly lower in the hangekobokuto group than in the placebo group (P = 0.017).…”
Section: Figure 11mentioning
confidence: 74%
“…The BHT group was able to maintain self-feeding better than the control group (P = .006). Very recently, the suppressing effect of BHT for aspiration pneumonia was confirmed by double blind RCT [12]. BHT was described in Jin kui Yao lue (金匱要略) by Zhan Zhong jing (張仲景) in 2nd century.…”
Section: Aspiration Pneumoniamentioning
confidence: 93%
“…[ 8 ] For patients in whom the swallowing reflex took longer than 4 s, banxia houpu tang (BHT), a specific type of traditional Chinese medicine reported to improve the swallowing reflex and reduce the risk of developing aspiration pneumonia, was administered. [ 7 9 10 ] We also collected data on their swallowing reflex time at baseline and after BHT treatment. We compared the group of patients who managed to recover to oral feeding (group 1) versus those who failed to resume this type of feeding (group 2).…”
Section: Methodsmentioning
confidence: 99%